Precise monitoring of mesenchymal stem cell homing to injured kidney with an activatable aptamer probe generated by cell-SELEX. (March 2021) - Zou, Yujian; Wen, Xiaohong; Ling, Dan; Zhang, Dongshan; Lei, Lei; Zhu, Dan; Wang, Honghui; Wang, Kemin; Guo, Qiuping; Nie, Hemin
Highlights: Deficiency of precise tracking tools to monitor MSCs has bottlenecked the clinical translation of stem cell therapies. An aptamer, termed seq3, with high specificy and affinity for mouse bone marrow MSCs was selected. Seq3-based activatable aptamer probes (AAP) were developed to monitor transpanted mBMSCs in a mouse model of chronic kidney disease. AAP substantially minimize the background signals and avoid the presence of false and/or false negative results. Seq3-AAP-based fluorescence imaging was promising for determing the survival status of transplanted mBMSCs. Abstract: Deficiency of precise tracking tools to monitor the migration and survival status of mesenchymal stem cells (MSCs) in the animal body has bottlenecked the clinical translation of stem cell therapies. In this study, we have for the first time successfully screened an aptamer, termed seq3, with high specificity and affinity for mouse bone marrow MSCs (mBMSCs) by MSC-based systematic evolution of ligands by exponential enrichment (MSC-SELEX), and ingeniously designed seq3-based activatable aptamer probes (AAP) for live-cell tracking. As proof of concept, real-time monitoring of transplanted mBMSCs in a mouse model of chronic kidney disease (CKD) was performed with the AAPs, and compared with Fe3 O4 -based magnetic resonance imaging (MRI), a widely utilized cell imaging module. It was confirmed that seq3 specifically binds to mBMSCs in the animal body and the binding activates the fluorescence of otherwise quenched dyes in AAPs, substantially minimizing the background signals originating from non-target tissues and avoiding the presence of false positive and/or false negative results occurred in MR imaging. Furthermore, the seq3-AAP-based fluorescence imaging was advantageous over Fe3 O4 -based MR imaging in terms of indicating survival status of the migrating and colonized mBMSCs, critical information required to evaluate the effectiveness and efficiency of cell therapy strategies. AAP fluorescence imaging results showed that the transplanted mBMSCs were well distributed in the bodies of normal mice and mainly aggregated in the livers, while they tended to migrate to injured kidneys of CKD mice and facilitated the repair of kidneys as a result. Besides cell tracking, the high specificity and affinity of seq3 to mBMSCs can be widely explored to understand the fate and biological roles of stem cells in regenerating tissues in the future. Graphical abstract: Image, graphical abstract